Spinal Cord Belt (MSB) as a Method of Reducing the Level of Low Back Pain in Cashier Pos Ticket Worker at Panakkukang Mall in Makassar (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background. PT.Centerpark in collaboration with Panakkukang Makassar Mall is a formal companyengaged in providing parking services. Worker in this company wrork every day with an average of 8 hoursa day, in a day worker is able to sit for 7 hours. So the risk of complaints pos ticket workers is very high.The purpose of this study was to determine the effect of using MSB on decrasing complaints of low backpain in the cash register cashiers at Panakkukang Mall Makassar in 2019. This study used pre and post teststo assess the level of low back pain in workers. Material and Method. The type of research used was anexperimental quasi. The sampling method uses simple purposive sampling. The study was conducted inNovember - February 2020. The number of sampling was 30 people. The data analysis technique used inthis study is Chi-square and Mann Whitney test. Results. The results showed that as The average level oflow back pain before and after the use of MSB in the intervention group before using MSB the mean valueis 4.93 mg/dl (SD = 1.03) after using MSB the mean value is 2.53 mg/dl (SD = 0.91). The use of MSB on thelevel of low back pain after treatment in the intervention group p (0,000) < p (0.05). The use of MSB on thelevel of low back pain after treatment in the control group was p (0,317) > p (0.05). There was a differencein changes in the scale of low back pain before and after using MSB in the intervention and control groups p(0,000) <p (0.05). Conclusion. There is a difference in the average level of the lower back before and afterthe use of MSB on the basis of the time before the use of MSB the average value of the worker level is 4.93mg/dl (SD = 1.03) after using MSB 53 mg/dl (SD = 0.91). It is recommended for workers to use MSB toolsevery time they work.